Volumetric staging in radiotherapy for oropharyngeal cancers. Issue 6 (December 2022) - Miszczyk, Marcin; Staniewska, Emilia; Jabłońska, Iwona; Lipka-Rajwa, Aleksandra; Stawiski, Konrad; Tarnawski, Rafał
Introduction: Despite routine use of 3D radiotherapy planning in radical radio(chemo)therapy for oropharyngeal cancers, volumetric data have not been implemented in initial staging. We analyzed 228 oropharyngeal cancer cases treated at one institution between 2004 and 2014 to compare the predictive value of volumetric staging and tumor nodal metastasis staging system (TNM) and determine whether they could be complementary for the estimation of survival. Methods: This retrospective study analyzed 228 consecutive oropharyngeal cancer cases treated with radiotherapy (76.9%) or concurrent radiochemotherapy (23.1%) between 2004 and 2014. The volumetric parameters included primary gross tumor volume (pGTV), metastatic lymph nodes gross tumor volume (nGTV), and total gross tumor volume (tGTV), and were compared with the 7th edition of the TNM staging system. Results: Median overall survival (OS) was 30.3 months. In the receiver operating characteristic analysis, tGTV had the highest area under the curve (AUC) of 0.66, followed by pGTV (AUC, 0.64), nGTV (AUC 0.62), and TNM (AUC 0.6). The median OS for patients with tGTV ⩽32.2 mL was 40.5 months, compared to 15.4 months for >32.2 mL ( p < 0.001). This threshold allowed for a statistically significant difference in survival between TNM stage IV cases with low and high tumor volume ( p < 0.001). Despite both TNM and tGTV reaching statistical significance in univariate analysis, only the tGTV remained an independent prognostic factor in the multivariate analysis (hazard ratio 1.07, confidence interval 1.02–1.12, p = 0.008). Conclusions: tGTV is an independent prognostic factor, characterized by a higher discriminatory value than the TNM staging system, and can be used to further divide stage IV cases into subgroups with significantly different prognosis.